The egg model – a geological ensemble for reservoir simulation. (November 2014) - Jansen, J. D.; Fonseca, R. M.; Kahrobaei, S.; Siraj, M. M.; Van Essen, G. M.; Van den Hof, P. M. J.
<x xml:space="preserve">Abstract</x> The 'Egg Model' is a synthetic reservoir model consisting of an ensemble of 101 relatively small three‐dimensional realizations of a channelized oil reservoir produced under water flooding conditions with eight water injectors and four oil producers. It has been used in numerous publications to demonstrate a variety of aspects related to computer‐assisted flooding optimization and history matching. Unfortunately the details of the parameter settings are not always identical and not always fully documented in several of these publications. We present a 'standard version' of the Egg Model which is meant to serve as a test case in future publications, and a dataset of 100 permeability realizations in addition to the permeability field used for the standard model. We implemented and tested the model in four reservoir simulators: Dynamo/Mores (Shell), Eclipse (Schlumberger), AD‐GPRS (Stanford University) and MRST (Sintef), which produced near‐identical output. This article describes the input parameters of the standard model. Together with the input files for the various simulators, it has been be uploaded in the 3TU.Datacentrum repository with free access to external users.